Community mobilisation in the 21st century: Updating our theory of social change?. (January 2014) - Campbell, Catherine
The article explores the Freirian theory of social change underpinning health-related community mobilisation in poor and marginalised communities. Highlighting potential shortcomings of its essentialist understandings of power and identity, and linear notions of change, it examines how lessons from the 'new left', and burgeoning global protest movements, can rejuvenate the field given the growing complexity of 21st-century social inequalities. It suggests the need for a pastiche of approaches to accommodate health struggles in different times and places. However, while needing some updating, Freire's profound and actionable understandings of the symbolic and material dimensions of social inequalities remain a powerful starting point for activism.